The Role of Critical Thinking in Enhancing Student Learning and Problem Solving for 21st-Century Challenges. - Bara, Enkelejda; Berdica, Brilanda; Bara, Gëzim (International Journal of Social Sciences & Humanities (IJSSH), 2025)
In today's changing world, students face multifaceted challenges that require more than rote memorization or basic understanding. Critical thinking (CRT) has become a crucial competency that enhances learning and problem-solving abilities, enabling students to address complex academic and real-life issues effectively. This research investigates the role of CRT in improving pupils' problem-solving skills and learning outcomes to prepare them for contemporary challenges better. Using a mixedmethods approach, 345 pupils were randomly assigned to control and experimental groups. A targeted CRT training program was implemented for the experimental group in order to improve their learning and problem-solving abilities. Additionally, a structured questionnaire gathered the demographic and self-reported data on CRT applications. Statistical analyses, including the Pearson correlation, paired ttests, and chi-square tests, were performed using SPSS software. Results demonstrated a significant improvement in the analytical reasoning, cognitive flexibility, and solution-oriented skills in the experimental group, with no notable changes in the control group. Participants reported increased confidence in opposing academic pressures and challenges such as cognitive and emotional barriers, educational system constraints, and uncertain environments. The findings underscore the importance of integrating CRT into educational programs to foster adaptive and reflective learners.